Draft genome sequence of arthrobacter enclensis NCIM 5488T for secondary metabolism - Neurgaonkar, P. S.; Dharne, M. S.; Dastager, S. G. (Genome Announcements, 2016)
Here, we report the draft genome sequence of Arthrobacter enclensis NCIM 5488T, an actinobacterium isolated from a marine sediment sample from Chorao Island, Goa, India. This draft genome sequence consists of 4,226,231 bp with a G+C content of 67.08%, 3,888 protein-coding genes, 50 tRNAs, and 10 rRNAs. Analysis of the genome using bioinformatics tools such as antiSMASH and NaPDoS showed the presence of many unique natural product biosynthetic gene clusters.